Composite catalysts containing gold nanoparticles incorporated in a porous support
The composite catalyst with gold nanoparticles in a porous support, optimized by a specific radial distribution function, addresses the issue of catalytic activity decline in existing catalysts, achieving high and stable conversion of reactant gases at room temperature and high flow rates.
Patent Information
- Application Number
- JP2024557801
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-28
- Filing Date
- 2022-12-29
- Publication Date
- 2025-04-22
AI Technical Summary
Existing composite catalysts supported on mesoporous materials suffer from aggregation and sintering of transition metal nanoparticles at high temperatures, leading to a decrease in catalytic activity and inefficient conversion of reactant gases at high flow rates.
A composite catalyst is developed with gold nanoparticles embedded in a porous support, characterized by a specific radial distribution function obtained from EXAFS spectra, which ensures optimal dispersion and stability of gold nanoparticles, thereby maintaining high catalytic activity even at room temperature and high flow rates.
The catalyst exhibits remarkably excellent catalytic activity at room temperature, enabling rapid conversion of all reactant gases to product gases at high flow rates, while maintaining high conversion efficiency and long-term stability without the need for high temperatures.
Smart Images

Figure 2025512874000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite catalyst comprising gold nanoparticles incorporated in a porous support, which has remarkably excellent catalytic activity at room temperature and can rapidly convert substantially all of a reactant gas contained in a gas flowing at a high flow rate at room temperature into a product gas. [Background technology]
[0002] Transition metal nanoparticles can exhibit catalytic activity due to their high specific surface area, but transition metal nanoparticles supported on a support have the problem that aggregation and sintering occur during a long-term reaction, reducing the specific surface area of the transition metal nanoparticles and gradually decreasing the catalytic activity. For this reason, research has been conducted on incorporating nanoparticles into the pores of metal oxide supports, but similarly, when exposed to high temperatures for a long period of time, the nanoparticles desorb from the pore surfaces and aggregate and sinter, and the problem of reduced catalytic activity could not be solved.
[0003] Transition metal nanoparticles generally have an average particle size of 20 nm or less as primary particles, and therefore a mesoporous support having a pore size of 2 to 50 nm is considered to be preferable for supporting such nanoparticles. The mesoporous support may be made of a metal oxide material, and typically known materials include silica, aluminosilicate, and titania. Mesopores of various sizes and shapes can be formed depending on the manufacturing method, and the acid site concentration and ion exchange capacity can be adjusted by adjusting the content of the metal or metalloid forming the framework. Thus, mesoporous supports are used as supports for transition metal nanoparticles, and have the advantage that the diffusion resistance of materials is lower and the reaction rate is faster than that of microporous supports due to the characteristics of the mesopores.
[0004] However, mesoporous supports carrying transition metal nanoparticles are generally operated at high temperatures, and therefore Ostwald ripening, particle migration, and coalescence easily occur, making it difficult to maintain catalytic activity for a long period of time, and thus making them uneconomical and difficult to implement. Accordingly, US 2019-0255520 A1 discloses a mesoporous silica support carrying gold nanoparticles that has catalytic activity at room temperature, but the catalytic activity is insufficient and the conversion rate is low at high flow rates. In particular, in air conditioning systems where the concentration of impurities must be controlled to extremely low levels, it is necessary to quickly remove all of the impurities, but since the conversion rate is acceptable only at or below a certain flow rate, it is necessary to develop a catalyst system with better room temperature catalytic activity. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] US 2019-0255520 A1(2019.08.22) [Patent Document 2] JP 2014-509927 A(2014.04.24) [Non-patent literature]
[0006] [Non-Patent Document 1] Topics in Catalysis 2007, Vol.44, Nos.1-2, pp.253-262. Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a composite catalyst having remarkably excellent catalytic activity at room temperature, specifically, to provide a composite catalyst capable of rapidly converting substantially all of the reactant gas contained in a gas into a product gas by flowing the gas at a high flow rate at room temperature.
[0008] Another object of the present invention is to provide a composite catalyst capable of removing substantially all of the harmful gases (impurities) contained in a gas at high speed, specifically, to provide a composite catalyst capable of removing substantially all of the harmful gases (impurities) contained in a gas by flowing the gas containing the harmful gases (impurities) at room temperature at a high flow rate.
[0009] Another object of the present invention is to provide a composite catalyst which has a very low gas diffusion resistance, can rapidly treat a gas with a high flow rate with a high conversion rate, does not require a high temperature to treat a gas with a high flow rate, and has an excellent catalytic activity for a long period of time. [Means for solving the problem]
[0010] In order to solve the above-mentioned problems, the present invention provides a composite catalyst comprising a porous support having mesopores and gold nanoparticles contained in the pores of the porous support, wherein a radial distribution function obtained by Fourier transform of an EXAFS (Extended X-ray absorption fine structure) spectrum satisfies the following formula 1: [Formula 1] (DH2 / DH1)<0.3 In the above formula 1, DH1 is the height of the peak at the interatomic distance D1, and DH2 is the height of the peak at the interatomic distance D2, where D1 and D2 respectively satisfy the following formulas 2 and 3: [Formula 2] 0.8≦(D1 / D3)≦0.95 [Formula 3] 0.6≦(D2 / D3)≦0.7 D3 in the above formulas 2 and 3 means the interatomic distance of the Au-Au bond in the bulk phase that is present at 2.8 to 3.0 Å.
[0011] In one embodiment, the composite catalyst may satisfy the following formula 4: [Formula 4] (DA2 / DA1)<0.25 In the above formula 4, DA1 is the area of the peak at the interatomic distance D1, DA2 is the area of the peak at the interatomic distance D2, and D1 and D2 satisfy the above formulas 2 and 3, respectively.
[0012] In one embodiment, (DH2 / DH1) in the above formula 1 can be 0.25 or less.
[0013] In one embodiment, (DA2 / DA1) in the above formula 4 may be less than or equal to 0.18.
[0014] In an embodiment, the composite catalyst may have a bimodal peak in an interatomic distance range of 2.2 to 3.0 Å in a radial distribution function obtained by Fourier transform of the EXAFS (Extended X-ray absorption fine structure) spectrum.
[0015] In one embodiment, the porous support may be a metal oxide or metalloid oxide porous support.
[0016] In one embodiment, the nanoparticles may have a diameter of 1 to 20 nm.
[0017] In one embodiment, the composite catalyst may further include macropores.
[0018] In one embodiment, the nanoparticles are incorporated into some of the mesopores of the porous support, and the mesopores not incorporating the nanoparticles may be interconnected by open pores.
[0019] In one embodiment, the composite catalyst may be for the oxidation reaction of carbon monoxide, aldehyde compounds, or hydrocarbon compounds.
[0020] In one embodiment, the composite catalyst can convert a gas containing carbon monoxide with a concentration of 4% into carbon dioxide with a conversion efficiency of 90% or more under a flow rate condition of 140 ml / min.
[0021] The present invention provides a method for removing harmful gases, comprising: supplying a gas stream containing one or more harmful gases selected from the group consisting of carbon monoxide, aldehyde compounds, and hydrocarbon compounds; and contacting the gas stream with the above-mentioned composite catalyst to oxidize the harmful gases.
[0022] In one embodiment, the oxidizing step may be performed at a temperature of 0°C to 60°C.
[0023] In one embodiment, the harmful gases can be removed by oxidation at a removal rate of 90% or more at a flow rate of 140 ml / min. Effect of the Invention
[0024] The composite catalyst according to the present invention can exhibit remarkably excellent catalytic activity at room temperature, and can rapidly convert substantially all of the reactant gas contained in the gas into product gas even when the gas is supplied at a high flow rate at room temperature.
[0025] In addition, the composite catalyst according to the present invention can rapidly remove substantially all of the harmful gases (impurities) contained in the gas, and can substantially remove all of the harmful gases (impurities) contained in the gas even when the gas containing the harmful gases (impurities) is supplied at room temperature and at a high flow rate.
[0026] In addition, the composite catalyst according to the present invention has an extremely low gas diffusion resistance, and can rapidly treat a gas with a high flow rate with a high conversion rate. It does not require a high temperature to treat a gas with a high flow rate, and has an excellent catalytic activity for a long period of time. [Brief description of the drawings]
[0027] [Figure 1]1 shows a radial distribution function obtained by Fourier transform of the EXAFS (Extended X-ray absorption fine structure) spectrum of the composite catalyst according to the present disclosure. [Diagram 2] 1 shows a radial distribution function obtained by Fourier transform of the EXAFS (Extended X-ray absorption fine structure) spectrum of the composite catalyst according to the present disclosure. [Diagram 3] 1 shows a radial distribution function obtained by Fourier transform of the EXAFS (Extended X-ray absorption fine structure) spectrum of the composite catalyst according to the present disclosure. [Figure 4] 1 shows a radial distribution function obtained by Fourier transform of the EXAFS (Extended X-ray absorption fine structure) spectrum of the composite catalyst according to the present disclosure. [Diagram 5] 1 shows a radial distribution function obtained by Fourier transform of the EXAFS (Extended X-ray absorption fine structure) spectrum of the composite catalyst according to the present disclosure. [Figure 6] FIG. 1 shows the conversion rate of carbon monoxide (CO) contained in a gas to carbon dioxide (CO2) by supplying the gas containing carbon monoxide (CO) to the composite catalyst according to the present disclosure at different flow rates. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Unless otherwise defined, technical and scientific terms used in this specification have the meanings commonly understood by a person of ordinary skill in the art to which the present invention belongs, and in the following description and accompanying drawings, descriptions of well-known functions and configurations that may unnecessarily obscure the gist of the present invention are omitted.
[0029] Also, as used herein, the singular forms "a," "an," and "the" can be intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0030] In addition, units used in this specification unless otherwise specified are based on weight, and for example, the unit of % or ratio means % by weight or weight ratio, and unless otherwise specified, % by weight means the weight % that any one component of the entire composition accounts for in the composition.
[0031] In addition, the numerical ranges used in this specification include lower and upper limits, and all values within the range, increments logically derived from the form and width of the defined range, all values limited therein, and all possible combinations of upper and lower limits of numerical ranges limited in different forms. Unless otherwise specified in the specification of the present invention, values outside the numerical range that may result from experimental error or rounding of values are also included in the defined numerical range.
[0032] As used herein, the term "comprising" is an open-ended term having the same meaning as expressions such as "comprising," "containing," "having," or "characterized by," and does not exclude further unrecited elements, materials, or steps.
[0033] The inventor first invented gold nanoparticle-supported mesoporous silica that has catalytic activity at room temperature, but the catalytic activity was insufficient, resulting in low conversion rate at high flow rates.In particular, impurities cannot be removed quickly to an acceptable level in air conditioning systems where the concentration of impurities must be controlled to a very small amount, so the inventor intensively researched to develop a composite catalyst with significantly superior catalytic activity. The present inventors have discovered that in the step of combining gold nanoparticles with a porous support, catalytic activity can be significantly improved by the correlation between the manufacturing process conditions and the radial distribution function, and have completed the present invention.
[0034] The composite catalyst according to the present disclosure includes a porous support having mesopores and gold nanoparticles contained in the pores of the porous support, and is characterized in that a radial distribution function obtained by Fourier transform of an EXAFS (Extended X-ray absorption fine structure) spectrum satisfies the following formula 1: [Formula 1] (DH2 / DH1)<0.3 In the above formula 1, DH1 is the height of the peak at the interatomic distance D1, and DH2 is the height of the peak at the interatomic distance D2, where D1 and D2 respectively satisfy the following formulas 2 and 3. Specifically, the above D1 and D2 are the interatomic distances of the maximum peaks found in the ranges which satisfy the following formulas 2 and 3, respectively. [Formula 2] 0.8≦(D1 / D3)≦0.95 [Formula 3] 0.6≦(D2 / D3)≦0.7 D3 in the above formulas 2 and 3 means the interatomic distance of the Au-Au bond in the bulk phase that is 2.8 to 3.0 Å, specifically, it may be 2.88 to 2.98 Å, and more specifically, it may mean the standard interatomic distance of 2.90 Å. Specifically, D3 may refer to the interatomic distance of the Au-Au bond in the bulk phase, which is present at 2.8 to 3.0 Å, obtained by peak deconvolution when the peak appears as one asymmetric peak or has a bimodal peak. The asymmetry means that the peak has a unimodal peak shape, but as the two peaks overlap, there is asymmetry on the left and right sides with respect to the center of the peak.
[0035] Specifically, (D1 / D3) in the above formula 2 can be 0.85 to 0.92, and (D2 / D3) in the above formula 3 can be 0.63 to 0.66.
[0036] According to a specific embodiment, DH1 in the above formula 1 may represent the height of a peak at an interatomic distance of 2.57±0.2 Å, and DH2 may represent the height of a peak at an interatomic distance of 1.85±0.2 Å. Specifically, DH1 may refer to the height of a peak at an interatomic distance of 2.57±0.1 Å, and DH2 may refer to the height of a peak at an interatomic distance of 1.85±0.1 Å.
[0037] When the composite catalyst satisfies the ratio of the height of the peak at the interatomic distance D1 to the height of the peak at the interatomic distance D2 of less than 0.3, the catalytic activity can be significantly improved.
[0038] EXAFS stands for extended X-ray absorption fine structure, which can analyze the radial distribution and coordination number of gold nanoparticles. For example, when high-energy X-rays are irradiated onto gold atoms, the gold atoms in the gold nanoparticles emit electrons. This generates a radial scattered wave centered on the gold atom that absorbed the X-ray, and when the electrons emitted from the gold atom that absorbed the X-ray reach an adjacent atom (gold or oxygen atom), an electron is emitted from the adjacent atom. At this time, a radial scattered wave is generated centered on the adjacent atom.
[0039] The scattered wave generated around the gold atom that absorbed the X-ray interferes with the scattered wave generated around the other adjacent atoms (gold or oxygen atoms). At this time, a standing wave is obtained according to the distance between the gold atom that absorbed the X-ray and the other atoms (gold or oxygen atoms) adjacent to the gold atom. When the standing wave is Fourier transformed, a radial distribution with a peak according to the distance between the gold atom and the other atoms (gold or oxygen atoms) adjacent to the gold atom is obtained. In other words, a radial distribution can be obtained that has not only a peak corresponding to the distance between gold (Au) atoms but also a peak corresponding to the distance between a gold (Au) atom and an oxygen atom having an Au-O bond when the gold (Au) atom has a bond with an oxygen atom.
[0040] According to an embodiment, (DH2 / DH1) in the above formula 1 may be less than or equal to 0.25, more specifically less than or equal to 0.24, and may be, without limitation, greater than or equal to 0. By having the above numerical range, the catalytic activity of the composite catalyst is significantly improved, which is preferable in that even in a gas stream with a high flow rate, substantially all of the reactant gas contained in the gas stream can be rapidly converted to product gas.
[0041] According to an embodiment, the composite catalyst may have a radial distribution function obtained by Fourier transforming an EXAFS (Extended X-ray absorption fine structure) spectrum that satisfies the following formula 4: [Formula 4] (DA2 / DA1)<0.25 In the above formula 4, DA1 is the area of the peak at the interatomic distance D1, DA2 is the area of the peak at the interatomic distance D2, and D1 and D2 satisfy the above formulas 2 and 3, respectively.
[0042] According to a specific embodiment, DA1 in the above formula 4 may be the area of a peak having an interatomic distance of 2.57±0.2 Å, and DA2 may be the area of a peak having an interatomic distance of 1.85±0.2 Å. Specifically, DA1 may refer to the area of the peak at an interatomic distance of 2.57±0.1 Å, and DA2 may refer to the area of the peak at an interatomic distance of 1.85±0.1 Å.
[0043] As the area ratio of the peak at the interatomic distance D1 to the peak at the interatomic distance D2 of the composite catalyst is less than 0.25, the catalytic activity can be significantly improved.
[0044] According to an embodiment, (DA2 / DA1) in the above formula 4 may be 0.2 or less, specifically 0.18 or less, more specifically 0.15 or less, and may be, but is not limited to, 0 or more. Within the above range, the catalytic activity is significantly improved, which is preferable in that the reactant gas contained in the gas stream can be rapidly and completely converted to the product gas even in a gas stream with a high flow rate.
[0045] According to an embodiment, the radial distribution function obtained by Fourier transforming the EXAFS (Extended X-ray absorption fine structure) spectrum may have a bimodal peak in an interatomic distance range of 2.2 to 3.0 Å, and the bimodal peak appears due to gold (Au)-gold (Au) atomic bonds. Specifically, the interatomic distance range of 2.2 to 3.0 Å may be a range in which the distance between gold (Au) atoms is located, and refers to the distribution of the interatomic distance of Au-Au in the crystal lattice.
[0046] Conventional gold nanoparticles can show a single peak in the interatomic distance range of 2.2 to 3.0 Å, and the fact that they have a single peak means that the gold (Au)-gold (Au) atomic distance is constant within the crystal lattice of the nanoparticles. However, the presence of a bimodal peak may mean that there are different Au-Au atomic distances in the crystal lattice, and although this has not been clearly determined, it is presumed that the two different Au-Au atomic distances were generated by deformation of the crystal lattice due to compressive stress. By having a bimodal peak in the interatomic distance range of 2.2 to 3.0 Å, it is possible to exhibit very excellent catalytic activity even in a low temperature region, and it is preferable in that the reactant gas contained in a high flow rate gas stream can be converted substantially entirely into the product gas very quickly.
[0047] According to an embodiment, the porous support may be a metal oxide or metalloid oxide porous support. The metal or metalloid of the metal oxide or metalloid oxide may be selected from groups 2 to 5, 7 to 9, and 11 to 14, specifically, a metal or metalloid selected from groups 2 to 4, 13, and 14, more specifically, Al, Ti, Zr, or Si.
[0048] The porous support includes mesopores and may optionally further include micropores. In the present disclosure, micropores means that the average diameter of the internal pores is less than 2 nm, and mesopores means that the average diameter of the internal pores is 2 nm to 50 nm. The volume of the mesopores in the porous support may be 50% by volume or more, 60% by volume or more, or 70% by volume or more, and there is no upper limit, but it may be, for example, 100% by volume or less, 95% by volume or less, or 90% by volume or less, or it may be 50 to 100% by volume, specifically 60 to 90% by volume, but this is only one example and is not limited thereto.
[0049] According to a non-limiting example, the porous support may have a hierarchical porous structure, and may include a structure in which micropores are regularly present and interconnected between mesopores.
[0050] According to a non-limiting embodiment, the porous support may further include macropores, and it is preferable that the porous support includes macropores at a certain volume fraction or more, since the gas diffusion resistance can be significantly reduced.
[0051] The gold nanoparticles can be prepared by methods known in the art or can be commercially available materials. Specifically, the gold nanoparticles can be prepared by reducing a gold precursor present in a solution to gold according to a known method (Natan et al., Anal. Chem. 67, 735 (1995)). The gold precursor may be, but is not limited to, a gold-containing halide, nitrate, acetate, acetylacetonate, or ammonium salt, etc. Specifically, the gold precursor may be, but is not limited to, HAuCl4 or HAuBr4.
[0052] The diameter of the gold nanoparticles may be 1 to 20 nm, specifically 1 to 15 nm, and more specifically 1 to 12 nm. The preferred diameter of the gold nanoparticles is 1 to 10 nm, and more preferably 1 to 8 nm.
[0053] According to an embodiment, the average diameter of the nanoparticles may be larger than the average diameter of the mesopores of the porous support, which may cause deformation of the crystal lattice of the gold nanoparticles contained in the mesopores of the porous support, thereby leading to improvement of catalytic activity at room temperature.
[0054] According to an embodiment, the nanoparticles may be incorporated into all or some of the mesopores of the porous support, more specifically, into some of the mesopores of the porous support, and more specifically, into some of the mesopores of the porous support in an irregular manner. In this case, the structure in which nanoparticles are contained in all of the mesopores of the porous support means a superlattice structure, specifically, a highly ordered superlattice structure having face-centered cubic (FCC) symmetry. The form in which nanoparticles are irregularly contained in some of the mesopores has an advantage that gas diffusion can be performed more effectively than the superlattice structure.
[0055] According to one embodiment, the nanoparticles may be incorporated into some of the mesopores of the porous support, and the mesopores not containing nanoparticles may be connected to each other through open pores. In the composite catalyst, the nanoparticles are incorporated into only some of the pores of the porous support, so that harmful gases can be more effectively diffused through the pores not containing nanoparticles that are connected to the open pores. Thus, even when the gas is supplied at room temperature and at a high flow rate, the reactant gas contained in the gas can be rapidly and completely converted into the product gas.
[0056] According to an embodiment, the composite catalyst may have an average particle size of 0.01 μm to 10 μm, specifically 0.05 μm to 5 μm, and more specifically 0.1 μm to 5 μm, but is not limited thereto.
[0057] According to an embodiment, the composite catalyst may be used in an oxidation reaction of carbon monoxide, an aldehyde-based compound, or a hydrocarbon-based compound. Thus, the composite catalyst according to the present disclosure may be preferably used as a solid-phase oxidant for carbon monoxide, an aldehyde-based compound, or a hydrocarbon-based compound. The aldehyde compound may be, but is not limited to, acetaldehyde or formaldehyde. The hydrocarbon-based compound may be an aliphatic or aromatic compound or a volatile organic compound (VOC), and examples thereof include, but are not limited to, methane, ethane, propane, butane, benzene, toluene, or xylene.
[0058] According to one embodiment, the composite catalyst can convert a 4% carbon monoxide-containing gas into carbon dioxide at a conversion efficiency of 80% or more, specifically 85% or more, more specifically 90% or more at room temperature under a flow rate of 140 ml / min. The carbon monoxide-containing gas may contain a certain amount of oxygen to be oxidized, for example, 2% or more, 4% or more, 10% or more, but not limited to 30% or less. For example, the carbon monoxide-containing gas may be air, but is not limited thereto as long as it contains a certain amount of oxygen or more.
[0059] The present invention provides a method for removing harmful gases, comprising: a step of supplying a gas stream containing one or more harmful gases selected from the group consisting of carbon monoxide, aldehyde compounds, and hydrocarbon compounds; and a step of contacting the gas stream with the composite catalyst according to any one of claims 1 to 11 to oxidize the harmful gases. In the above-mentioned method for removing harmful gases, by using the composite catalyst exhibiting remarkably excellent catalytic activity as described above, oxidation reactions can occur more effectively in gas streams having a high flow rate at room temperature.
[0060] According to an embodiment, the oxidation step may be performed at a temperature of 0°C to 60°C, specifically 10°C to 50°C, and more specifically 20°C to 40°C, but is not necessarily limited thereto.
[0061] According to an embodiment, the harmful gases can be removed by oxidation at a removal rate of 80% or more, specifically 85% or more, more specifically 90% or more, at a flow rate of 140 ml / min. Specifically, the harmful gases can be removed at a removal rate in the above-mentioned temperature range.
[0062] According to an embodiment, the harmful gases may be removed by an oxidation reaction at a removal rate of 80% or more, specifically 85% or more, more specifically 90% or more, and even more specifically 95% or more at a flow rate of 160 ml / min. Specifically, the harmful gases may be removed at the removal rates in the above-mentioned temperature ranges. EXAMPLES
[0063] The present disclosure will be described in more detail below using examples. However, the following examples are provided to aid in understanding the present application, and the contents of the present application are not limited to the following examples.
[0064] Example 1: Preparation of Composite Catalyst 1 [Step 1]: Preparation of polymer-functionalized gold nanoparticles [Step 1-1]: Oleylamine-stabilized gold nanoparticles are synthesized by the following procedure.
[0065] First, oleylamine was selected as the stabilizer, and a solution consisting of 60 ml of tetralin, 60 ml of oleylamine, and 0.6 g of HAuCl HO was prepared by stirring at room temperature for 10 minutes. 6 mmol of TBAB (tetrabutylammonium bromide), 6 ml of tetralin, and 6 ml of oleylamine were mixed by ultrasonic pulverization and quickly added to the above solution. The solution was stirred at room temperature for another hour, ethanol was added, and the solution was centrifuged to precipitate the gold nanoparticles. The gold nanoparticle precipitate was redispersed in hexane, and ethanol was added and centrifuged. The gold nanoparticles produced showed an average particle size of 4 nm, and the produced gold nanoparticles were dispersed in 100 ml of toluene as they were formed.
[0066] [Step 1-2]: The surface of gold nanoparticles is functionalized with thiolated PEG via the following method. The gold nanoparticles dispersed in toluene in step 1-1 above were further diluted with 100 ml of tetrahydrofuran, and a thiolated polymer was selected to functionalize the surface of the gold nanoparticles by binding the polymer to them, and 1 g of monofunctional polyethylene glycol substituted with a thiol group at the end (aSH-PEG, weight average molecular weight: 1 kDa) was added. After stirring, hexane was added and centrifuged to precipitate PEG-functionalized gold nanoparticles (4-Au-PEG). The 4-Au-PEG obtained by precipitation was dried and then dispersed in water.
[0067] [Step 2]: Preparation of PEG-functionalized gold nanoparticle-entrapped porous silica 0.088 g of 4-Au-PEG prepared in step 1-2 above was mixed with 0.396 g of Pluronic F127 as an activator, and uniformly dispersed in 10 ml of 1.6 M HCl aqueous solution, and then 1.49 g of tetraethyl orthosilicate (TEOS) was added to the dispersion. The mixture dispersion was stirred for 15 minutes and then maintained at room temperature for 40 hours without stirring to produce a red precipitate. The red precipitate thus formed corresponds to the porous silica in which PEG-functionalized gold nanoparticles were trapped.
[0068] [Step 3]: Preparation of composite catalyst The red precipitate produced in the previous step was washed with water, dried, and then calcined stepwise at 250°C for 3 hours, 400°C for 2 hours, and 500°C for 2 hours to remove PEG and Pluronic F127 polymer, thereby producing composite catalyst 1, which is porous silica with gold nanoparticles trapped therein.
[0069] Example 2: Preparation of Composite Catalyst 2 Composite catalyst 2, which is a porous silica having gold nanoparticles encapsulated therein, was prepared by carrying out the same steps as in step 1-1 of Example 1, except that gold nanoparticles having an average particle size of 10 nm were prepared by adjusting the molar ratio of oleylamine and HAuCl HO.
[0070] Example 3: Preparation of Composite Catalyst 3 Composite catalyst 3 was prepared by carrying out steps 1 and 3 in the same manner as in Example 1, except that step 2 was carried out as follows.
[0071] To prepare porous alumina with PEG-functionalized gold nanoparticles in step 2, 0.15 g of PEG-functionalized gold nanoparticles (4-Au-PEG) and 0.675 g of Pluronic F127 were prepared and uniformly dispersed in a mixture of 0.8 ml of nitric acid (68%) and 40 ml of ethanol, and then 0.81 g of aluminum ethoxide was added to the dispersion. The mixture dispersion was stirred for 3 hours, and then maintained at room temperature for 24 hours without stirring, and then dried at 60° C. for 3 hours to prepare a red solid. Then, step 3 of Example 1 was carried out in the same manner to prepare composite catalyst 3, which is porous alumina having gold nanoparticles trapped therein.
[0072] Example 4: Preparation of Composite Catalyst 4 Composite catalyst 4 was prepared by carrying out steps 1 and 3 in the same manner as in Example 1, except that step 2 was carried out as follows.
[0073] To prepare porous titania with PEG-functionalized gold nanoparticles in step 2, 0.10 g of PEG-functionalized gold nanoparticles (4-Au-PEG) and 0.44 g of Pluronic F127 were prepared and uniformly dispersed in a mixture of 0.68 ml of 37% hydrochloric acid and 17.05 ml of ethanol, and then 2.28 g of titanium tetraisopropoxide was added to the dispersion. The mixture dispersion was stirred for 3 hours, maintained at room temperature for 24 hours without stirring, and then dried at 60° C. for 3 hours to produce a red solid. Then, step 3 of Example 1 was carried out in the same manner to produce composite catalyst 4, which is porous titania having gold nanoparticles trapped therein.
[0074] Comparative Example 1 Steps 1 and 2 were carried out in the same manner as in step 1-1 of Example 1, except that the molar ratio of oleamine and HAuCl·H2O was adjusted to prepare gold nanoparticles having an average particle size of 12 nm. In step 3, the red precipitate prepared in the previous step was washed with water, dried, and then calcined at 450°C to remove PEG and Pluronic F127 polymer, thereby preparing composite catalyst 5, which is porous silica with gold nanoparticles trapped therein.
[0075] Comparative Example 2 Steps 1 and 2 were carried out as in Example 1 above. In step 3, the red precipitate produced in the previous step was washed with water, dried, and then calcined at 450°C to remove PEG and Pluronic F127 polymer, thereby producing composite catalyst 6, which is porous silica with gold nanoparticles trapped therein.
[0076] (Experimental Example 1) EXAFS (Extended X-ray absorption fine structure) analysis Extended X-ray absorption fine structure (EXAFS) measurements were performed using the 4C and 10C beamlines at the Pohang Accelerator Laboratory (PLS-II). The EXAFS spectra were Fourier transformed to obtain the radial distribution function.
[0077] FIG. 1 shows the radial distribution functions of Example 1, FIG. 2 shows the radial distribution functions of Example 2, FIG. 3 shows the radial distribution functions of Example 3, FIG. 4 shows the radial distribution functions of Example 4, and FIG. 5 shows the radial distribution functions of Comparative Example 1. Referring to these, a peak due to Au-O bonds was observed in the 1.4 to 1.7 Å range in all of FIGS. 1 to 5. From this, it can be confirmed that the proximity between the surface of the gold nanoparticles and the porous support that captures them provides the conditions for the formation of stable Au-O bonds at the interface between the gold nanoparticles and the porous support, resulting in the formation of Au-O-Si, Au-O-Al, or Au-O-Ti.
[0078] In addition, in all of Figures 1 to 5, a peak due to bulk Au-Au bonds was observed in the 2.8 to 3.0 Å range, and when the interatomic distance of such a peak is defined as D3, the peak of the radial distribution function was defined based on D3. Specifically, D1 and D2 are the interatomic distances of the maximum peaks found in the range satisfying the following formulas 2 and 3, respectively, and the positions of D1, D2, and D3 are shown in Table 1. In addition, the ratios of the peak height (DH1) and area (DA1) of the interatomic distance D1 to the peak height (DH2) and area (DA2) of the interatomic distance D2 were calculated and shown in Table 1. [Formula 2] 0.8≦(D1 / D3)≦0.95 [Formula 3] 0.6≦(D2 / D3)≦0.7
[0079] [Table 1]
[0080] (Experimental Example 2) Oxidation characteristics of carbon monoxide Carbon monoxide (CO) oxidation was carried out in a tubular reactor with both sides open. The composite catalysts according to the present disclosure and comparative examples were installed in the middle of the tubular reactor, a carbon monoxide-containing gas was supplied to one side of the reactor, and the other side of the reactor was connected to Gas Chromatography (DS Science) to measure the carbon monoxide concentration with a TCD detector (Carboxen 1000). The carbon monoxide-containing gas was 4% CO, 10% O2, and 86% He, and the concentration of carbon monoxide discharged to the other side of the reactor was measured while adjusting the supply flow rate at room temperature (25° C.) The measurements were performed using the composite catalysts according to Example 1, Example 2, and Comparative Example 1, and the results are shown in FIG.
[0081] Referring to FIG. 6, 4 nm means Example 1, 10 nm means Example 2, and 12 nm means Comparative Example 1. Example 1 showed a carbon monoxide conversion rate of nearly 100% even at a high flow rate, while Example 2 showed a partial decrease in conversion rate at a high flow rate, but showed a conversion rate of 90% or more even at a flow rate of 140 ml / min. In contrast, in Comparative Example 1, the conversion rate decreased rapidly at high flow rates, and showed a conversion rate of less than 70% at a flow rate of 160 ml / min, indicating that the catalyst does not have sufficient catalytic activity at high flow rates.
[0082] As above, the present invention has been described with reference to specific matters and limited examples and drawings, but these are provided to facilitate a more complete understanding of the present invention, and the present invention is not limited to the above examples. Various modifications and variations are possible from such base materials if one has ordinary knowledge in the field to which the present invention pertains.
[0083] Therefore, the concept of the present invention should not be limited to the described embodiments, and all modifications equivalent to or equivalent to the scope of the claims, including but not limited to the scope of the claims described below, belong to the concept of the present invention.
Claims
1. A porous support containing mesopores and gold nanoparticles contained within the pores of the porous support; The radial distribution function obtained by Fourier transform of the EXAFS (Extended X-ray absorption fine structure) spectrum satisfies the following formula 1, composite catalyst: [Formula 1] (DH2 / DH1)<0.3 In the above formula 1, DH1 is the height of a peak at an interatomic distance D1, DH2 is the height of a peak at an interatomic distance D2, and D1 and D2 respectively satisfy the following formulas 2 and 3: [Formula 2] 0.8≦(D1 / D3)≦0.95 [Formula 3] 0.6≦(D2 / D3)≦0.7 D3 in the formulas 2 and 3 means the interatomic distance of the Au-Au bond in the bulk phase, which is present in the range of 2.8 to 3.0 Å.
2. The composite catalyst of claim 1 satisfies the following formula 4: [Formula 4] (DA2 / DA1)<0.25 In the formula 4, DA1 is the area of the peak at the interatomic distance D1, DA2 is the area of the peak at the interatomic distance D2, and D1 and D2 satisfy the formulas 2 and 3, respectively.
3. 2. The composite catalyst according to claim 1, wherein (DH2 / DH1) in formula 1 is 0.25 or less.
4. 3. The composite catalyst according to claim 2, wherein (DA2 / DA1) in formula 4 is 0.18 or less.
5. The composite catalyst according to claim 1, wherein the radial distribution function obtained by Fourier transform of the EXAFS (Extended X-ray absorption fine structure) spectrum has a bimodal peak in an interatomic distance range of 2.2 to 3.0 Å.
6. 10. The composite catalyst of claim 1, wherein the porous support is a metal oxide or semi-metal oxide porous support.
7. The composite catalyst of claim 1, wherein the nanoparticles have a diameter of 1 to 20 nm.
8. The composite catalyst of claim 1 , wherein the composite catalyst further comprises macropores.
9. 2. The composite catalyst of claim 1, wherein the nanoparticles are incorporated into a portion of the mesopores of the porous support, and the mesopores not containing the nanoparticles are interconnected by open pores.
10. 2. The composite catalyst according to claim 1, which is for the oxidation reaction of carbon monoxide, aldehyde compounds or hydrocarbon compounds.
11. 11. The composite catalyst according to claim 10, wherein the composite catalyst converts a carbon monoxide-containing gas having a concentration of 4% into carbon dioxide with a conversion efficiency of 90% or more at a flow rate of 140 ml / min.
12. providing a gas stream containing one or more harmful gases selected from the group consisting of carbon monoxide, aldehydes, and hydrocarbons; and 12. A method for removing harmful gases comprising: contacting the gas stream with the composite catalyst of any one of claims 1 to 11 to oxidize the harmful gases.
13. The method for removing harmful gases according to claim 12, wherein the oxidizing step is performed at a temperature of 0°C to 60°C.
14. 13. The method for removing harmful gases according to claim 12, wherein the harmful gases are removed by oxidation reaction at a removal rate of 90% or more under a flow rate condition of 140 ml / min.
Citation Information
Patent Citations
Gold-supported titanium dioxide nano-catalyst as well as preparation method and application of gold-supported titanium dioxide nano-catalyst
CN104353456A
Porous composite carrying metal ultra fine particle
JP2006247524A
Metallic nanoparticle catalysts embedded in porous oxide support, which show high catalytic activity even at low temperatures
WO2020197200A1
Method for preparing spherical materials having hierarchical porosity, including metal particles trapped in a mesostructured matrix.
JP2014509927A
Gold nanoparticle superlattice embedded in porous silica and method for manufacturing same
US20190255520A1